Floating Backup Supply Using Solar - Shahrir, Mohammad Afiq Izzuddin; Aziz, Roziah (Evolution in Electrical and Electronic Engineering, 2023)
Nowadays, floods often happen in Malaysia everywhere. Areas that are often affected by floods such as states on the east coast will flood once a year. The state is an area that is difficult to avoid this problem of flooding. If there is a flood in many areas, electricity will be cut off from the main electricity supply. Therefore, it will be difficult for flood victims to get help. Thus, this floating, solar-powered emergency power supply was created. This energy supply will receive energy supply through solar which is from the reflection of light. The received solar energy will store its energy in the battery and will be used for the phone to get help. In addition, this energy supply can also be used for lighting purposes. A lamp that uses a USB adapter can be used to provide light to users to protect themselves from the darkness.